Pengaruh Permeabilitas dan Konsentrasi Polimer terhadap Saturasi Minyak Sisa pada Injeksi Polimer - Avty Vilanti; Sugianto Kasmungin; Dwi Atty Mardiana (President University, 2017)
Polymer injection is one of the methods of increasing oil recovery or Enhanced Oil Recovery (EOR) after the water injection method is performed, to reduce residual oil saturation. The polymer reduces the water mobility ratio so that the sweeping efficiency will increase to encourage bypassed and unswept residual oil saturation. For polymer injection applications, partially hydrolyzed polyacrylamide (PHPA) or commercially known as HPAM is the most widely used type. At the current low oil prices, design optimization of polymer injections in certain reservoirs is important. The purpose of this research is to analyze the effect of permeability and polymer concentration on residual oil saturation by core flooding method in the effort of optimization of polymer injection. The optimal concentration in this study is 1,500 ppm which has the lowest residual oil saturation value. The increase in concentration from 500 ppm to 1.500 ppm, residual oil saturation decreased in four variations of Berea sandstone permeabilities. However, when the polymer concentration is added to 2.500 ppm, the residual oil saturation value increases. This can be caused by pore clogging. Whereas with permeability, residual oil saturation is directly proportional. The greater the permeability the greater the value of residual oil saturation. Core Y7 Berea has the highest permeability and saturation of residual oil. The results of this study are expected to be useful in the development of polymer injections on EOR activity.Keywords. polymer injection, concentration, permeability, PHPA, residual oil saturation